A whole class teaching approach to improve the vocabulary skills of adolescents attending mainstream secondary school, in areas of socioeconomic disadvantage. (June 2017) - Murphy, Aoife; Franklin, Sue; Breen, Annemarie; Hanlon, Molly; McNamara, Aoife; Bogue, Aine; James, Emily
Young people from areas of socioeconomic disadvantage (SED) are more likely to present with language difficulties, particularly vocabulary difficulties. Studies have shown the effectiveness of vocabulary interventions for children with language impairment but not for adolescents from areas of SED. This article aims to establish the effectiveness of a whole class vocabulary intervention provided by teachers, with speech and language therapy support for adolescents in secondary schools in areas of SED. Two hundred and three adolescents (aged 11;11–13;11) from four secondary schools were assessed at pre-intervention and post-intervention on measures of receptive and expressive language; word definitions; receptive vocabulary (standardized assessments/subtests) and word associations (criterion referenced subtest). The intervention group ( n = 128) received the intervention delivered by their English teacher twice a week for 12 weeks in the first school term and were compared with a group of waiting controls ( n = 75). Waiting controls were given the intervention in the second school term and were assessed a third time in a repeated measures design. At pre-intervention stage 37%–60% of all students scored in the vocabulary difficulties range on all assessments. Following intervention, the treated group showed significant, but small, time by group interactions for raw score measures of expressive language and receptive vocabulary. The intervention group improved significantly on all four standardized measures; waiting controls improved on two: receptive language and word definitions. There were no significant time by group interactions. Following receiving intervention waiting controls showed significant interactions for all raw score and expressive language, word definitions and receptive vocabulary standard/scaled score measures. The findings suggest that adolescents in schools in areas of SED present with significant vocabulary difficulties, but whole class teacher-directed intervention supported by speech and language therapists has the potential to improve receptive and expressive oral vocabulary skills.